Inteligência artificial, cultura e cinema: análise estilístico-narrativa de A.I. de Steven Spielberg - Verri, Carolina de Souza (2024)
This present work is a film analyzes of A.I.: Artificial Intelligence (2001) directed by Steven Spielberg, in order to understand how the film gender of science fiction updates the structure of the monomyth, as defined by Joseph Campbell (2007). For this reason, the study investigates the stylistic devices shown by the mise en scène and its levels of meaning. The film analyses are segmented into acts, allowing the film to raise its on questions. Additionally, the film’s narrative structure is analyzed bases on the concepts of Robert McKee (2018), taking into account the characterization and function of the protagonist, David, during the narrative. In parallel, the development of the character’s dramatic arc is also examined through the stages of the monomyth and its archetypes, as described by Jung (2023). Similarities were identified between the archetype of the divine child and the role that the protagonist fulfills with the narrative’s resolution. Framings of David underneath circular forms revels that the film’s stylistics choices follows the typical representations of this archetype, which is often associated with circular figures. The analysis of the stylistic elements also brought to attention the recurring presence of water throughout David’s journey, whose symbolic meaning is interpreted through Gaston Bachelard’s (2018) work. Through the analysis, the intertextuality within the film and within Spielberg’s work becomes evident. This is not only due to the film’s inspiration from Brian Aldiss short story Super toys Last All Summer Long (2001) but also due to how the narrative references the story of Pinocchio. Intertextuality is also manifested in the narrative conventions of the classical cinema and of the cinema of science fiction. The theme of creating an artificial intelligence capable of surpassing its creators is often shown in science fiction literature and cinema. Such cultural products points to the impact of new technologies on the field of cultural studies. Thus, this study seeks to understand how science fiction movies updates the structure of the monomyth to address contemporary themes and universal questions about humanity and the relationship between creator and creature on the field of artificial intelligence.